Variabilidade glicêmica, estabilidade de membrana eritrocitária e marcadores de estresse oxidativo em pacientes com diabetes mellitus tipo 1 - Rodrigues, Ricardo (2017)
Glycemic variability, erythrocyte membrane stability and oxidative stress markers in patients with type 1 diabetes mellitus Introduction: Glycemic variability (GV) has been described as an independent risk factor for chronic complications of diabetes. Objectives: To evaluate glycemic variability among DM1 patients and to study possible correlations of GV with cell membrane stability parameters and with oxidative stress markers. Material and Methods: We studied 90 patients with DM1 undergoing intensive treatment. The evaluations included: anthropometric indexes, biochemical measurements (glucose, uric acid, lipidogram, glycated hemoglobin, microalbuminuria, creatinine and iron), complete blood count and reticulocytes, calculations of membrane stability parameters and dosages of oxidative stress markers (thiobarbituric acid reactive substances and reduced glutathione). All sets of values were analyzed for distribution. Values with normal distribution were expressed as mean and standard deviation and compared with t-test for independent samples, while values with non-normal distribution were expressed in median and interquartile range and compared with the Mann-Whitney test. Data correlation analyzes with normal and non-normal distribution were done using the Pearson or Spearman methods, respectively. Values of p less than 0.05 were considered statistically significant. Results: The standard deviation (SD) of the daily glycemic mean (DAG) was 89.8 (72-111) mg/dL and presented a strong linear correlation with HbA1c levels (ρ = 0.63, p <0.0001). Markers of short-term and long-term glycemic variability (SD and ΔHbA1c, respectively) showed correlations with membrane stability parameters and analysis of these same parameters between the subgroups of lower GV versus higher GV also showed statistically significant differences. The activity of glutathione reductase (GR), a marker of oxidative stress, showed a correlation with GV (r = 0.4 and p < 0.05). Conclusion: Glycemic variability in individuals with DM1, even under intensive treatment, is of great intensity and presents a direct correlation with glycated hemoglobin levels, and can be used as a tool in the identification of patients who are more likely to fail to achieve good control goals. GV also showed correlations with some parameters of erythrocyte membrane stability, reinforcing the existence of potential role of these cells in the mechanisms related to the development of chronic complications of diabetes.